Impacto económico de los convenios de doble tributación en la inversión extranjera directa. Caso Ecuador - Jácome Padilla, Lucy Marlene (2014)
This research examines whether double taxation agreements are an incentive to attract foreign investment to Ecuador from economically and fiscally. The first and second chapters deal with the research variables, the theoretical framework for foreign direct investment, modalities, the contribution in developing countries, and double taxation agreements, international taxation concept, methods of double taxation models of agreements. While in the third chapter analyzes government policies on FDI in recent decades that have affected the economy of Ecuador by reference to the gross domestic product is made. The fourth chapter presents statistical data on foreign direct investment before and after the signing of double taxation agreements it has signed with Ecuador fifteen countries. In conclusion, according to the analysis of the behavior of FDI from Ecuador the primary sector leaves a negative impact due to the extraction of natural resources, damage to the environment and there is no transfer of knowledge and technology is one of the advantages of maintaining IED. From the side of taxation with the signing of the CDI, no increased incidence in attracting greater FDI flows, despite maintaining agreed fifteen double taxation, they do not reflect increased foreign investment, and the type of model agreement (OECD) where the tax authority is in the country of origin and not on the source, Ecuador forgone taxes that can be invested in infrastructure, health and education.